Novel sounds, native responses: exploring the acoustic consequences of Eleutherodactylus johnstonei’s invasion in urban areas - Melo, Natalia Bispo Vieira; Both, Camila; Brasileiro, Cinthia A. (Frontiers in Amphibian and Reptile Science, 2024)
Biological invasions pose a significant threat to biodiversity, impacting ecological balance. Exotic species using acoustic communication can disrupt native species' communication by interfering with the acoustic niche. Eleutherodactylus johnstonei, an exotic anuran in São Paulo, has males whose vocalizations serve as a pronounced source of environmental noise, overlapping with native species. Acknowledging that noise can lead to acoustic masking, we investigated the effects of E. johnstonei's acoustic niche invasion on the calls of two native species: Scinax imbegue and Physalaemus cuvieri, emitting vocalizations with and without spectral overlap with the exotic species. We created playbacks with E. johnstonei's vocalization, the native Boana bischoffi (control), and white noise, altering stimuli order for six versions. Playbacks were conducted for S. imbegue and P. cuvieri males in the field, recording response calls and noting behavioral changes. E. johnstonei's vocalization didn't alter spectral and temporal parameters of native species' announcement calls. However, S. imbegue males ceased vocalizing or moved away from the noise source. Additionally, B. bischoffi's calls and white noise altered native species' call parameters. These findings highlight the potential influence of novel sounds on individuals' acoustic behavior. The impact of exotic species' calls varies across species and contexts. Further studies with species vocalizing at different frequencies and in diverse acoustic landscapes are crucial for understanding anuran patterns.